Does It Matter that Quantitative Analysis Cannot Deal with Theatrical Performance? - Pechter, Edward (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2020)
The question in my title takes off from the longstanding controversy in Shakespeare studies between literary and theatrical value. I am interested in the claim that a digitally based quantitative approach, while it may have a limited purchase on the ephemeral and transient effects of theatrical performance, is nonetheless well positioned to analyze the stable effects of theatrical texts. The assumption behind this claim, that the linguistic features which constitute texts may be counted as if every instance of a given feature produces effects identical to every other, is, I think, mistaken. Words may of course be treated as data, but textual effects do not inhere in the quantifiable properties of textual objects; they depend on the actions of interpreting subjects. From this angle, textual effects, however differently produced from theatrical effects, are similarly unstable, and quantitative analysis is not suited to the interpretation of either one. This in no way diminishes the achievements of quantitative practitioners, of which attribution – untangling numerous webs of collaborative authorship and assigning a proliferation of Renaissance playtexts, orphaned at birth, to authorial homes – is only the most spectacular recent example. But to treat numbers as meaning, to take the processing of data as if in itself it produces interpretive conclusions, extends quantitative analysis into areas outside its own jurisdiction. Such expansive designs are damaging in the first instance to the overreachers themselves; unfulfillable promises reinforce the suspicions that sequester quantitative analysis in a negligible space. The damage extends to the technoskeptics on the other side as well, who will find themselves confirmed in their prejudices and therefore even less likely to take advantage of the real benefits a digitally based quantitative approach makes available to all Shakespeareans. Keywords: Theatrical effects, Textual effects, Interpretation